Economic Analysis of Panitumumab Compared With Cetuximab in Patients With Wild-type KRAS Metastatic Colorectal Cancer That Progressed After Standard Chemotherapy - Graham, Christopher N.; Maglinte, Gregory A.; Schwartzberg, Lee S.; Price, Timothy J.; Knox, Hediyyih N.; Hechmati, Guy; Hjelmgren, Jonas; Barber, Beth; Fakih, Marwan G. (Clinical therapeutics, 2016)
In this analysis, we compared costs and explored the cost-effectiveness of subsequent-line treatment with cetuximab or panitumumab in patients with wild-type KRAS (exon 2) metastatic colorectal cancer (mCRC) after previous chemotherapy treatment failure. Data were used from ASPECCT (A Study of Panitumumab Efficacy and Safety Compared to Cetuximab in Patients With KRAS Wild-Type Metastatic Colorectal Cancer), a Phase III, head-to-head randomized noninferiority study comparing the efficacy and safety of panitumumab and cetuximab in this population. A decision-analytic model was developed to perform a cost-minimization analysis and a semi-Markov model was created to evaluate the cost-effectiveness of panitumumab monotherapy versus cetuximab monotherapy in chemotherapy-resistant wild-type KRAS (exon 2) mCRC. The cost-minimization model assumed equivalent efficacy (progression-free survival) based on data from ASPECCT. The cost-effectiveness analysis was conducted with the full information (uncertainty) from ASPECCT. Both analyses were conducted from a US third-party payer perspective and calculated average anti–epidermal growth factor receptor doses from ASPECCT. Costs associated with drug acquisition, treatment administration (every 2 weeks for panitumumab, weekly for cetuximab), and incidence of infusion reactions were estimated in both models. The cost-effectiveness model also included physician visits, disease progression monitoring, best supportive care, and end-of-life costs and utility weights estimated from EuroQol 5-Dimension questionnaire responses from ASPECCT. The cost-minimization model results demonstrated lower projected costs for patients who received panitumumab versus cetuximab, with a projected cost savings of $9468 (16.5%) per panitumumab-treated patient. In the cost-effectiveness model, the incremental cost per quality-adjusted life-year gained revealed panitumumab to be less costly, with marginally better outcomes than cetuximab. These economic analyses comparing panitumumab and cetuximab in chemorefractory wild-type KRAS (exon 2) mCRC suggest benefits in favor of panitumumab. ClinicalTrials.gov identifier: NCT01001377.